Effect of Eu Doping on the Physical, Photoluminescence, and Photocatalytic Characteristics of ZnO Thin Films Grown by Sol–Gel Method. Issue 12 (24th October 2017) - Sanchez Rayes, R. M.; Kumar, Y.; Cortes‐Jácome, M. A; Toledo Antonio, J. A.; Mathew, X.; Mathews, N. R
Abstract : Eu doping concentration driven effect on the morphological, electrical, and optical properties of ZnO films prepared by sol gel method have been studied systematically. The properties of the films were studied using various experimental tools such as XRD, AFM, XPS, photoconductivity, UV–vis spectroscopy, photoluminescence (PL), and photocatalytic activity. Eu incorporation into the ZnO lattice was confirmed by XPS analysis. A decrease in crystallite size with increasing Eu concentration was observed. PL spectra showed that Eu‐ related light emission intensity reached a maximum at 6 wt.%. Photoconductivity measurements showed maximum photosensitivity for 4 wt.% Eu doped film. The photocatalytic activity of Eu‐ doped films was evaluated for methylene blue degradation and is found to be maximum for 6 wt.% Eu doped film. Abstract : This work is focused on understanding the effect of Europium doping concentration on the modifications of structural, electrical, and optical properties of ZnO thin films, prepared by simple chemical method on top of glass substrates. The important result is the increase in photosensitivity and photocatalytic efficiency with the europium doping concentration, which demonstrates its potential applications in the field of photocatalysis.